Una pinza de cierre automático - Doval, Juan Carlos Federico; Panelo, Armando; Pensotti, Antonio Carlos; Vega, Aníbal Rogelio; Ferrando, Juan Carlos (1977)
Fil: Doval, Juan Carlos Federico. Comisión Nacional de Energía Atómica; Argentina.